Primeros auxilios y soporte vital básico a los estudiantes de Primero y Segundo Año de Bachillerato Paralelo "E" del Colegio Beatriz Cueva de Ayora de la ciudad de Loja. - Ortega Cabrera, Karina Elizabeth (2017)
The main objective of this research was to determine the level knowledge about First Aid and Basic Life Support in first and second year of high school students, grade “E” in “Beatriz Cueva de Ayora” High School in Loja City. The study was descriptive, transversal, prospective, intervention and field. To collect data was applied one questionnaire of fifteen multiple choice questions to seventeen students, which are sample. The results obtained allow concluding that students have little knowledge of the issues evaluated, since in the initial diagnostic test 49.17 % of right answers were obtained, and the final diagnostic test 98.31% right answers were obtained, increasing by 49.14% the level of knowledge of students. Thus it was carried out the intervention, aimed at training on First Aid and Basic Life Support in theoretical and practical lessons, using didactic and audiovisual materials. It allowed choosing two students of grade “E” to form the brigade school, which will be prepared to help in the different emergency situations that may occur inside and outside school. Key words: First Aid, Basic Vital Support, high school, knowledge.